Equilibrium, Kinetics, and Thermodynamic Studies Concerning the Removal of 2–chlorophenol Using Chemically Carbonized Rice Husk Waste - Channei, Duangdao; Nakaruk, Auppatham; Khanitchaidecha, Wilawan; Jannoey, Panatda; Phanichphant, Sukon (Naresuan University Journal: Science and Technology (NUJST), 2020)
In this work, the adsorption of a harmful pollutant, 2–chlorophenol, from aqueous solution onto carbonized rice husk (C–RH) was investigated. Highly-porous adsorbent C–RH was produced in this study using chemical activation with hydrochloric acid, followed by carbonization at 550°C. The surface morphology of C–RH by scanning electron microscope (SEM) and BET N 2 adsorption/desorption techniques showed that the results of C–RH characterization had a pore volume of 0.042 cm 3 /g and BET surface area of 278.90 m 2 /g due to the resulting silicon element contained in rice husk ash. Pore size distribution having a clear hysteresis loop belongs to type IV isotherm nature with H3–type of hysteresis loop, which is distributed by pores mainly in the mesoporous range. The batch adsorption experiments showed that the equilibrium uptake was increased with an increase in initial 2–chlorophenol concentration. The experimental isotherm data fit better with the Freundlich isotherm model, which followed an ideal multilayer adsorption with the maximum monolayer adsorption capacity (N m ) of 13.4048 mg/g obtained by Langmuir. Kinetic data was best fit to a pseudo–second order rate equation, indicating chemisorption. Thermodynamic parameter in terms of ΔG o for the adsorption showed that adsorption on the surface of C–RH at 304.15 K was spontaneous in nature. Consequently, C-RH produced from rice husk waste has the potential to serve as an alternative to commercial activated carbon for water treatment.   Keywords: Mesopore, Rice husk, Freundlich model, Adsorption, 2–chlorophenol